Stirrings : how activist New Yorkers ignited a movement for food justice - Povitz, Lana Dee (Justice, power, and politics., 2019)
"In the last three decades of the twentieth century, government cutbacks, stagnating wages, AIDS, and gentrification pushed ever more people into poverty, and hunger reached levels unseen since the Depression. In response, New Yorkers set the stage for a nationwide food justice movement. Whether organizing school lunch campaigns, establishing food co-ops, or lobbying city officials, citizen-activists made food a political issue, uniting communities across lines of difference. The charismatic, usually female leaders of these efforts were often products of earlier movements: American communism, civil rights activism, feminism, even Eastern mysticism. Situating food justice within these rich lineages, Lana Dee Povitz demonstrates how grassroots activism continued to thrive, even as it was transformed by unrelenting erosion of the country's already fragile social safety net. Using dozens of new oral histories and archives, Povitz reveals the colorful characters who worked behind the scenes to build and sustain the movement, and illuminates how people worked together to overturn hierarchies rooted in class and race, reorienting the history of food activism as a community-based response to austerity. The first book-length history of food activism in a major American city, Stirrings highlights the emotional, intimate, and interpersonal aspects of social movement culture"--Publisher's description